Missed nursing care and its related factors from the points of view of nurses affiliated to Kerman University of Medical Sciences in 2017 - Rahimmeh Khajooee; Behnaz Bagherian; Mahlagha Dehghan; Mansooreh Azizzadeh Forouzi (Tehran University of Medical Sciences, 2019)
Background & Aim: Nursing care is an essential part of health care services. Missed nursing care is a new concept referring to any aspect of care, that is omitted or delayed. The present study aimed to assess missed nursing care and its related factors from the viewpoints of nurses working in the hospitals affiliated to Kerman University of Medical Sciences in 2017. Methods & Materials: In this descriptive, cross-sectional study, 300 nurses participated. Two questionnaires on missed nursing care, and its related factors were used for data collection. Data were analyzed through the SPSS software version 20 using descriptive indices. Results: The mean score of missed nursing care was 32.28±7.41, which was lower than the median (range) of the questionnaire. The highest mean score of missed nursing care and its related factor, respectively were "attending the interprofessional patient care conferences" and "the volume of activities related to patients' admission and discharge". Conclusion: The level of missed nursing care was lower than the median in the present study, which can be lowered by proper management. In addition, by decreasing nurses' workload, missed nursing care related factors can be reduced.